The Influence of Facilities and Infrastructure on the Effectiveness of Employee Work at PDAM Tirtanadi, Sunggal Branch, Medan - Riskiyanti, Laila; Wulandari, Sri Eka (Cattleya Darmaya Fortuna, 2024)
This research discusses the influence of facilities and infrastructure on the work effectiveness of PDAM Tirtanadi Sunggal Branch employees. The purpose of this research is to determine the influence of facilities and infrastructure (X) on employee work effectiveness (Y). This research uses indicators from each variable. The indicators for facilities and infrastructure (X) are Equipment, Supplies, Infrastructure. Indicators of work effectiveness (Y) are goal achievement, work quality, work quantity, punctuality, job satisfaction. This research uses quantitative methods with a population of 46 people and a sample of 46 people, while for managing research data using the SPSS version 23 program. Based on the research results, it can be seen that the facilities and infrastructure variables partially have a significant effect on the work effectiveness variable as proven by the results of the T test with a calculated t value of 10.154 > t table 1.680 and a significant value of 0.000 < 0.05. The results of the simple linear regression test which has the equation Y = 36.876 + 0.783 show that the facilities and infrastructure variable shows a coefficient value of 0.783, which means that the facilities and infrastructure variable has a positive influence on the work effectiveness variable. The results of the coefficient of determination test show that the value (R square) obtained is 0.701 (70.1%) indicating that facilities and infrastructure have an influence on employee work effectiveness by 70.1%.